Complete mitochondrial genome sequence of Pleurobranchaea novaezealandiae and Pleurobranchaea sp. Issue 1 (1st January 2016) - Chen, Liu; Yang, Tiezhu; Shen, Heding
Abstract: The complete mitochondrial genome sequences of Pleurobranchaea novaezealandiae and Pleurobranchaea sp. are first described and analyzed in this study. It is 14, 531 bp and 14, 709 bp in length, respectively. The base composition of the genome with A + T bias are 66.41% and 68.36%. There are 29 noncoding regions found throughout the mitogenome of P. novaezealandiae and 30 noncoding in Pleurobranchaea sp., ranging in size from 2 to 294 bp. The phylogenetic tree based on 10 mitogenome, including 1 prosobranchia, 6 opisthobranchia and 3 pulmonata was analyzed in the paper. The results showed that the opisthobranchia and pulmonata were clustered respectively, and the P. novaezealandiae and Pleurobranchaea sp. were the closest to the Aplysia californica in our analysis.